2018
DOI: 10.15244/pjoes/85303
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Index Classification Model for Loess Deposits Based on Rough Set and BP Neural Network

Abstract: Classifying loess deposits is an important process for selecting support form and construction methods for tunnels. An accurate evaluation of loess deposits is a necessary prerequisite to control deformation, save cost, and improve construction efficiency. In this paper, a neural network model with an evaluation system consisting of physical and mechanical indices of loess is proposed to realize intelligent classification of loess deposits for tunneling. The influence of water content, natural density, cohesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Zhang et al thought that the responsibility of university in the new era is to enhance students' entrepreneurial awareness and EA and guide students to learn the skills of market operation in a reasonable curriculum system under the guidance of correct objectives, so as to enhance their ability to start their own businesses [17]. He et al believed that the emergence of innovative education is an educational idea accompanied by the rise of knowledge economy.…”
Section: Research Status Of College Students' Ea Evaluationmentioning
confidence: 99%
“…Zhang et al thought that the responsibility of university in the new era is to enhance students' entrepreneurial awareness and EA and guide students to learn the skills of market operation in a reasonable curriculum system under the guidance of correct objectives, so as to enhance their ability to start their own businesses [17]. He et al believed that the emergence of innovative education is an educational idea accompanied by the rise of knowledge economy.…”
Section: Research Status Of College Students' Ea Evaluationmentioning
confidence: 99%
“…Computational and Mathematical Methods in Medicine intelligent classification of loess deposits in tunnel engineering, Zhang and others proposed an evaluation system based on BP neural network, which was applied to practical analysis and showed that the model output results were consistent with the actual results [29].…”
Section: Bp Neural Networkmentioning
confidence: 82%
“…The results show that the overall accuracy of the fault diagnosis model based on the improved BP neural network is as high as 98.3% [ 28 ]. In order to realize the intelligent classification of loess deposits in tunnel engineering, Zhang and others proposed an evaluation system based on BP neural network, which was applied to practical analysis and showed that the model output results were consistent with the actual results [ 29 ].…”
Section: Related Workmentioning
confidence: 99%
“…e trained BPNN model is valid if the error is within this range, ending the training process. If the error is not within the set accuracy, then the inner coefficients in the hidden layers need to be modified again [27,28]. First, the input increment in the hidden layer is set by equations ( 17) and (18).…”
Section: Algorithm Process Of the Bpnnmentioning
confidence: 99%